PENGARUH PENGENDALIAN INTERNAL, KETAATAN ATURAN AKUNTANSI, DAN KOMPETENSI TERHADAP KECENDERUNGAN KECURANGAN PADA BPR SE-KABUPATEN GIANYAR - Agustina, Dea Ayu; Latrini, Made Yenni (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.07.TAHUN.2024, 2024)
This study aims to determine the effect of internal control, obedience of accounting rule, and competence at BPR in Gianyar Regency. The population in this study is all employees of the BPR in Gianyar Regency. The research sample was 119 respondents by determining the sample using purposive sampling method. Collecting data using a survey method with questionnare as a research instrument. Analysis of data that uses in this study using the program SmartPLS 3.0. The PLS technique was used to test hypotheses in two steps, examining both the outer and inner models. To demonstrate the reliability and validity of each indicator in each model variable, an outer model test was conducted and a test of the inner model was run to see how the model's variables affected the assumptions that were previously established. The results showed that the variables of internal control and obedience of accounting rule has a negative effect on tendency of fraud, and the variable of competence has no effect on tendency of fraud. The implication of this research is internal control system, obedience of accounting rule, and competence of employees must be implemented properly and in accordance with the rules to minimize the tendency of fraud.